Republic of Belarus : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of Belarus. (IMF Staff Country Reports; Country Report ;, 2019)
The Belarusian economy is in a cyclical recovery, inflation is at historically low levels and the exchange rate has been broadly stable. Although macroeconomic policy frameworks have improved, there is a need to reduce deep seated vulnerabilities such as rapidly rising public debt, high dollarization, and limited trade and financing diversification. In addition, reforms of the large state-owned enterprise sector are critical to tackle inefficiencies and increase potential growth. Risks ahead are elevated; notably, Belarus could lose significant oil-related discounts and transfers due to internal tax changes in Russia, but the authorities are confident of a successful outcome to the ongoing negotiations.